Finite element modelling of pulsed eddy current non-destructive testing for different defect natures - Nafiah, Faris; Sophian, Ali; Khan, Md. Raisuddin; zainal abidin, Ilham Mukriz (MINES ParisTech Centre, 2017)
Pulsed eddy current (PEC) has attracted researchers of various backgrounds in the attempt to optimize the benefits of this method in Non-destructive Testing (NDT). With various means of approach in solving PEC problems, a correlation between Finite Element Modeling (FEM) and experimental study has to be done. Three cracks of different natures have been 3D modelled using COMSOL Multiphysics 5.2a and verified experimentally. The results involve taking the signals at different positions away from the middle of the opening of the cracks. Different trends employed by different natures of defect are also presented in the paper